Analysis of health literacy instruments which could be used on a primary healthcare level - Ubavić Stana; Krajnović Dušanka; Marinković Valentina (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2015)
Health literacy measurement means appliance of different instruments which determine the degree of understanding of read and written information, as well as numerical skills necessary for making relevant health decisions. The objective of this study is to identify instruments which are used to measure health literacy at a primary healthcare level, to compare them and analyze their structure in order to examine their relevance for health literacy evaluation in public pharmacies. Collection of data related to health literacy is done by literature search, and for every instrument for measuring health literacy given is its content and description of performance and conditions for use (with special view if it is applicable in pharmacy settings). Analysis of instruments is done by method of comparison. There were identified 5 instruments for direct measuring of health literacy and each could be used in pharmacy settings. It was concluded that the NVS (Newest Vital Sign) which measures functional and critical health literacy in a very short time would be the most suitable instrument for health literacy measurement in pharmacy settings.